The Clinical Implications of Spontaneous Hemorrhage in Vestibular Schwannomas - Hong, Christopher S.; Jin, Lan; David, Wyatt B.; Shear, Brian; Zhao, Amy Y.; Zhang, Yawei; Erson-Omay, E. Zeynep; Fulbright, Robert K.; Huttner, Anita; Kveton, John; Moliterno, Jennifer (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Spontaneous hemorrhage into vestibular schwannomas (VSs) is rare and can render more rapid symptom onset and a seemingly poorer prognosis for an otherwise benign pathology. We describe our series of hemorrhagic VS (HVSs) and systematically reviewed the literature to better understand relevant clinical factors and outcomes.Methods Retrospective case review series and systematic review of the literature using PRISMA guidelines.Results Fifty-three patients with HVS met inclusion criteria. Compared with historical data for all VS, patients with HVS had relatively higher rates of perioperative mortality, significant preoperative facial weakness, and harbored relatively larger tumors. Regardless of the extent of resection (EOR), surgery for HVS resulted in significant improvement of facial weakness (p = 0.041), facial numbness (p < 0.001), vertigo (p < 0.001), and headache (p < 0.001). Patients with facial weakness tended to have larger tumors (p = 0.058) on average and demonstrated significant improvement after surgery, irrespective of EOR (p < 0.01). The use of blood-thinning medications did not affect patient health outcome. Histopathology of HVS samples showed an increased number of dilated/ectatic thin-walled vascular channels, reflective of potentially increased vascular permeability and hypervascularity.Conclusion HVS may be an aggressive subgroup of VS, associated with a surprisingly high mortality rate. When features of HVS are identified on imaging, these patients should be treated expeditiously, especially given that facial nerve dysfunction, which is identified in more than half of patients with HVS, appears to be reversible. Overall, this study has significant implications in the management of VS, raising awareness of a small, but highly morbid subgroup.
Keywords: vestibular schwannoma; acoustic neuroma; hemorrhage; coagulopathy